Green and Facile Reaction of Gabapentin with Sulfonyl Chlorides to Synthesize Lactams and Sulfonamides Derivatives in Aqueous Medium - Hussain, Erum A.; Kanwal, Nosheen; Khan, Islam Ullah; Mutahir, Sadaf; Khan, Muhammad Asim; Ahmed, Maqsood; Mahmood, Arshad; Sahin, Onur; Akkurt, Mehmet; Yar, Muhammad (Letters in Organic Chemistry, 2018)
In the current research, a facile and green one pot synthesis of new gabapentin-lactams (G2-G8) has been achieved by reacting gabapentin (G1) with a variety of sulfonyl chlorides. The new lactamization protocol is furnished under the green solvent i.e., water and reaction was completed in a short period of time by just stirring at room temperature. Whereas in some cases, annulation could not happen and furnished un-cyclized sulfonamide products (G9-G12). The structures of the targeted compounds were established by elemental analysis, FT-IR, 1H-NMR and mass spectrometry. The crystals of some new lactams (G2, G3, G4, and G8) were also evaluated by single crystal X-ray diffraction.
Keywords: sulfonamides